The call of the wild and white fang ebook - London, Jack (Sterling Unabridged Classics., 2011)
The illustrations for this series were created by Scott McKowen, who, with his wife Christina Poddubiuk, operates Punch & Judy Inc., a company specializing in design and illustration for theater and performing arts. Their projects often involve research into the visual aspects of historical settings and characters. Christina is a theater set and costume designer and contributed advice on the period clothing for the illustrations. Scott created these drawings in scratchboard an engraving medium which evokes the look of popular art from the period of these stories. Scratchboard is an illustration board with a specifically prepared surface of hard white chalk. A thin layer of black ink is rolled over the surface, and lines are drawn by hand with a sharp knife by scraping through the ink layer to expose the white surface underneath. The finished drawings are then scanned and the color is added digitally. Two of Jack London's best-loved masterpieces, in their entirety. Call of the Wild tells a compelling tale of adventure during the Yukon Gold Rush, and fully captures the unquenchable spirit of Buck, a kidnapped dog trying to survive in the harshest of environments. Also set in Alaska, the powerful White Fang follows the often savage life of the magnificent title character, a mix of wolf and dog.